Affect as a multimodal practice. Issue 1 (March 2021) - Westberg, Gustav
This paper sets out a framework for analyzing affect as a multimodal practice. The overall objective is to contribute to the theoretical development of how affect can be approached as an object of semiotic enquiry. The framework is based on the assumption that affect is semiotically materialized through discourse, and with the ambition of taking multimodality seriously, subject formation, strategic perspectivation and affordance are proposed as conceptual starting points for the study of affective meaning-making. Examples are drawn from artifacts and images that represent the Sámi as desirable objects to consumers and tourists. Through a detailed semiotic analysis of a pair of jeans described as being Sámi inspired, and through an analysis of images that promote Sámi tourism experiences, the paper demonstrates how affective ways of being emerge in a relationship between the affordance of semiotic materials and different subjectivities. These insights point to the possibility of further investigating affective subject formation as materialized in diverse semiotic materials in relation to other social phenomena, political issues and ideological concerns.